Mediation Role in Solving Sharia Economic Dispute as Civilization Toward Ethical Value of Islam - santoso, santoso (Sharia Faculty Islamic Economic Law Study Department, 2022)
The aim of this study is to explain the role of mediation in solving sharia economy dispute as civilization toward ethical value of Islam. That it has been practiced since Rasulullah SAW era was through many ways such as shulh, tahkim, and qadha. This study uses qualitative method and data collection is got from observation, direct interview to justice, attorney, lawyer, mediator, and the disputants. Based on the result of the study above is known that the role of mediation in solving sharia economy dispute as civilization toward ethical value of Islam is important and needs to be optimalized. According to Rasulullah SAW teaching, in fact, in a practice, there is failure of mediation in solving sharia economy dispute because the disputants feel that they are right and want to win finally by litigation way with consent or default judgment. Otherwise, mediation practice gives benefits for the disputants and based on Indonesian culture and civilization because solving dispute through mediation can be solved fast, correctly, and cheaply, thus it does not take much energy, time, and thought. In a result, it can keep privacy, beneficial for parties, and harmless with the result made by parties themselves, that is “win-win solution”. In ethical value of Islam in solving sharia economic dispute, firstly, by al-shulh (peace). Peace in islam is recommended because if there is peace among disputants, they will avoid from hostility. If it does not work, it can be passed by al-tahkim (arbitration) and if it gets stuck, Islam teaches us by al-qadha (Court Process).